Urgent Need to Orient Public Health Response to Rapid Nutrition Transition - Umesh Kapil; Harsh Pal Singh Sachdev (Wolters Kluwer Medknow Publications, 2012)
India is currently undergoing a rapid transition on economic, demographic, epidemiologic, nutrition, and sociological fronts. There is evidence of a decline in undernutrition with a simultaneous escalation in overnutrition and associated non-communicable diseases (NCDs). However, the current concern and national policy response for tackling malnutrition in India is still primarily restricted to undernutrition diagnosed on the basis of body size (anthropometry). A complex range of interacting factors have been linked to the rising trend of overnutrition and associated NCDs from a global perspective. The burden of overnutrition and associated morbidities is rapidly escalating to alarming proportions, particularly in urban areas and high socio-economic status groups. The poor are not spared from this transition. It is predicted that a more rapid transition may occur amongst poor populations in future with higher economic development. The need of the hour is to launch an integrated public health response to the dual burden beginning from pregnancy and early life. This will obviously require careful deliberation of the strategy and interventions, and a multi-sectoral approach, especially involving the health, women and child development, nutrition, education, agriculture, food processing, trade, architecture, water supply and sanitation, community and non-governmental organizations.